FRI0013 IL-22 Induces An Increase in SFP3 Expression by Synovial Fibroblasts in Inflammatory Joint Diseases. (15th July 2016) - Resende, G.; Machado, C.; Macedo, R.; Rocha, M.; Nascimento, V.; Bueno Filho, J.; Kakehasi, A.; Andrade, M.
Abstract : Background: Rheumatoid Arthritis (RA), Psoriatic Arthritis (PsA) and Ankylosing Spondylitis (AS) are inflammatory joint diseases (IJD) with different joint remodeling patterns [1]. TNFalfa, IL17 and IL22 indirectly through signaling pathways such as Wnt may play a role in these phenotypes distinctiveness [2, 3]. Fibroblast-like synoviocytes (FLS) have been considered an innate immunity component implicated in the switch of an acute and reparable to a chronic and persistent inflammatory process with irreversible tissue damage in that diseases [4]. Objectives: The aim of this study was to evaluate the expression of two Wnt pathway extracellular modulators (sFRP3 and DKK1) by FLS of patients with different IJD, in response to IL17, IL22 or TNFalfa. Additionally, we analyze the concentrations of all these proteins directly in the synovial fluid of inflamed peripheral joints. Methods: 25 patients with an IJD diagnosis and the indication of joint infiltration for disease activity, was selected, regardless their systemic treatment. FLS were cultivated from synovial fluid and this were also used to measure the concentrations of DKK1, sFRP3, TNFalfa, IL17 and IL22 by ELISA. DKK1 and sFRP3 levels were dosed in the supernatant of cell cultures after pro-inflammatory stimulation. Results: The concentrations of IL22 and sFRP3 were positively correlated (r=0.76; p<0.01) in synovial fluid and the highest levels were observed among TNFalfa inhibitors users (p=0.01). sFRP3 and DKK1 are constitutively expressed by FLS. Lower values of DKK1 were detected in PsA (p<0.01) as well as sFRP3 in AS (p=0.01). IL22 was the only cytokine able to increase sFRP3 production by these cells (p<0.01). No cytokine was efficient in increasing the expression of DKK1 in this study. Conclusions: The high positive correlation between IL22 and sFRP3 in the synovial fluid of inflamed joints may be explained by the fact of that cytokine was capable of increasing this modulator production by FLS, in this experiment. Since sFRP3 is a canonical Wnt inhibitor and it blocks the osteoblastogenesis, different responses to IL22 may imply in different patterns of structural damage and joint remodeling. References: Schett G. Joint remodelling in inflammatory disease. Annals of the rheumatic diseases. 2007;66 Suppl 3:iii42–4. Daoussis D, Andonopoulos AP, Liossis SN. Wnt pathway and IL-17: novel regulators of joint remodeling in rheumatic diseases. Looking beyond the RANK-RANKL-OPG axis. Seminars in arthritis and rheumatism. 2010;39(5):369–83. Lories RJ, McInnes IB. Primed for inflammation: enthesis-resident T cells. Nature medicine. 2012;18(7):1018–9. Buckley CD, Filer A, Haworth O, Parsonage G, Salmon M. Defining a role for fibroblasts in the persistence of chronic inflammatory joint disease. Annals of the rheumatic diseases. 2004;63 Suppl 2:ii92-ii5. Acknowledgement: to Research Support Fund of Brazilian Society of Rheumatology Disclosure of Interest: None declared